2016
DOI: 10.1163/18759866-08502003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental taxonomy exposes ontogenetic variability and elucidates the taxonomic value of claw configuration in MilnesiumDoyère, 1840 (Tardigrada: Eutardigrada: Apochela)

Abstract: Key words: barcoding, diagnostic key, development tracking, in vitro culture, M. berladnicorum, M. variefidum sp. nov. AbstractIn this paper we describe a new apochelan species, Milnesium variefidum sp. nov. from Scotland and provide novel morphological and molecular data for Milnesium berladnicorum Ciobanu et al., 2014. The new species differs from the most similar M. berladnicorum by the presence of developmental dimorphism in claw configuration, absent or weakly developed cuticular bars under claws I-III, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 42 publications
4
79
0
Order By: Relevance
“…It should be noted that “pseudopores” have been described from several species of Milnesium , showing that they are typically more numerous in adults than in juveniles (Kaczmarek, Jakubowska, & Michalczyk, ; Morek, Gąsiorek, Stec, Blagden, & Michalczyk, ). However, these pseudopores are actually intracuticular cavities, and their distribution pattern does not correspond to muscle attachment sites (Morek et al, ). Therefore, these characters are likely a property of the cuticle itself rather than any underlying structures and should not be homologized with the pores we describe herein.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that “pseudopores” have been described from several species of Milnesium , showing that they are typically more numerous in adults than in juveniles (Kaczmarek, Jakubowska, & Michalczyk, ; Morek, Gąsiorek, Stec, Blagden, & Michalczyk, ). However, these pseudopores are actually intracuticular cavities, and their distribution pattern does not correspond to muscle attachment sites (Morek et al, ). Therefore, these characters are likely a property of the cuticle itself rather than any underlying structures and should not be homologized with the pores we describe herein.…”
Section: Discussionmentioning
confidence: 99%
“…, as in M. tardigradum , see below) and between the second and the third instar (e.g. , as in M. variefidum Morek, Gąsiorek, Stec, Blagden, & Michalczyk, ), we suggest to use distinct and intuitive single‐word names to describe the two life stages: the hatchling and the juvenile for the first and the second instar, respectively. From the third instar onwards, individuals are sexually mature; thus, they should be referred to as adults .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in order to distinguish the time of the claw configuration change, we propose the terms early and late claw configuration change to describe the change occurring between the hatchling and the juvenile, and between the juvenile and the adult, respectively. Furthermore, as the number of points may increase (e.g., as in M. variefidum Morek, Gąsiorek, et al., ) or decrease (e.g., as in M. tardigradum , see below) during ontogenesis, we postulate to distinguish the direction of the claw configuration change by naming the increase as the positive , and the decrease as the negative claw configuration change . If needed, the position of the claw (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, no further details for the Milnesium specimens were included in his description, yet on the basis of the claw configuration it can be concluded that Murray’s Irish specimens are not Milnesium tardigradum sensu stricto or its subspecies and so this record must be listed in our Irish checklist as Milnesium sp. sensu Michalczyk et al (2012a, 2012b) and Morek et al (2016).…”
Section: James Murray and The Clare Island Surveymentioning
confidence: 99%